2020
DOI: 10.3390/ijerph17041444
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ambient Particulate Matter Exposure and Longitudinal Weight Growth Trajectories in Early Childhood

Abstract: Air pollution exposure during pregnancy has been associated with impaired fetal growth and postnatal weight gain, but few studies have examined the effect on weight growth trajectories. We examine the association between validated 1 km2 resolution particulate matter (PM2.5) concentrations, averaged over pregnancy, and sex-specific growth trajectories from birth to age six of participants in the Boston-based Children’s HealthWatch cohort (4797 participants, 84,283 measures). We compared weight trajectories, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
(89 reference statements)
4
16
1
Order By: Relevance
“…Upon examination of non-linearity, positive associations of particulate matter with infant body composition appeared to plateau beyond the first tertile of exposure. Consistent with previous studies [ 11 , 22 ], we observed sex-specific findings. O x wt was associated with change in umbilical circumference and a modestly larger increase in CTSF, with these associations observed only among females and males, respectively, following stratification by sex.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Upon examination of non-linearity, positive associations of particulate matter with infant body composition appeared to plateau beyond the first tertile of exposure. Consistent with previous studies [ 11 , 22 ], we observed sex-specific findings. O x wt was associated with change in umbilical circumference and a modestly larger increase in CTSF, with these associations observed only among females and males, respectively, following stratification by sex.…”
Section: Discussionsupporting
confidence: 93%
“…These covariates were chosen based on known associations with infant growth parameters and/or AAP exposure levels [ 34 ]. Based upon previous literature [ 11 ], infant sex was also examined as a potential effect modifier of the relationship between ambient air pollution and early infant growth. Sensitivity analyses were also performed, which additionally adjusted for birth weight and the baseline variable of each change outcome.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the situation seems more complex in humans, whose mothers are normally exposed to PM during both pre-conceptional and gestational periods. In humans, only girls show this predicted trend, whereas boys with intrauterine exposure to a higher level of PM remain underweight in childhood [ 60 ]. This may suggest that there is an additive effect between pre-conceptional and gestational exposures or even postnatal exposure, as babies normally live in the same environment as mothers.…”
Section: Disrupted Foetal Developmentmentioning
confidence: 99%